SMART ELEVATOR SYSTEM USING IMAGE PROCESSING - BUDIN, ARIF AKMAL (IRC, 2019)

(untitled)
Since public elevator was introduced by Elisha Otis in 1874 this vertical transportation has gone through a lot of improvement in its feature, efficiency, speed, and etc. Elevator has since be a favourite choice instead of stairs. However, waiting time is always the main issue for every elevator users especially in a high storey buildings. Hence, this project has proposed a smart system that implement image processing technology. Raspberry pi will be hosting this project aside from webcam as an input device and output device will be an Elevator Simulator mainly consist of LED , Push Button, and 7 Segment Display. The simulator will act as a 3 floor building with a hall call function. The image processing system will be tested by using simulation and real time method. The overall cost for this project is RM 181.60. Image processing system are able to detect the pedestrian using video file and webcam as input, also the elevator simulator with a hall call function are successfully developed, both of the system are then finally integrated .